Socio-economic parameters of functions of the territory of territorial communities in the context of spatial planning - Dorosh, O.; Dorosh, A.; Zastulka, I.-O. (Land Management, Cadastre and Land Monitoring, 2022)
The existing methods and parameters for determining the capacity and monitoring the development of territorial communities in ecological, economic and social sections are analysed. It was established that most of the methods and parameters are fundamental and involve a general assessment of community capacity and are not aimed at being indicators of the development of a separate territorial community in ecological, economic and social terms.It is proposed to use the parameters of the territory's functions as indicators of the development of territorial communities. The choice of the parameters of the territory's functions is based on the need, based on the aspects of spatial planning and spatial development, to plan the territory of the community in such a way that it performs its functions as efficiently as possible within its powers and capabilities. Based on the analysis of scientific works, the definition of the concept of "territory functions" is given and a list of their functions relevant within the framework of this study is formed.The list of parameters of the territory's functions is proposed and substantiated, it is indicated that the communities are able to partially provide them, and it is determined that they could serve as indicators of the development of territorial communities indirectly through the planning documentation of the territory of the community, and the method of their determination is proposed. The socio-economic parameters of the territory functions for the Chinadiiivska settlement territorial community of the Mukachivskyi raion of the Transcarpathian oblast have been determined.Key words: functions of the territory, parameters of the functions of the territory, indicators of the development of territorial communities, spatial planning of the territories of communities, spatial development.